Determinants of success in scaling B2b technology startups - Gümüs, Viktor Adnan (2022)
While there have been different studies on success factors for early-stage startups, little research has focused on the determinants of success in the scaling phase. This work aims to construct a broader vision of determinants of success, first by building a conceptual framework from literature, before then using LEDR as a case study to validate the results. The identified criteria to assess the suitability of a use case were customer, use case and implementation considerations, while internal scaling success factors are financial capability, clear strategic direction, scalable processes, people practices, management practices, product offering and marketing and sales.